2012
DOI: 10.1080/00140139.2012.663002
|View full text |Cite
|
Sign up to set email alerts
|

Trust in technology-mediated collaborative health encounters: Constructing trust in passive user interactions with technologies

Abstract: The present study investigated factors that explain patient trust in health technology and the relationship between patient trust in technology and trust in their care provider. Sociotechnical systems theory states that changes in one part of the system are likely related to other parts of the system. Therefore, attitudes about technologies, like trust, are likely related to other aspects of the system. Contributing to appropriate trust at the technological, interpersonal, and system levels can potentially lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 19 publications
(21 reference statements)
1
12
0
Order By: Relevance
“…In this way, our concept with its underlying statements contributes to a new understanding of eHealth literacy. The concept also includes subjects previously identified to be essential to ensure usage of health technology [ 35 , 36 ], that is, trust that is embedded in the domains “4. Access to technologies that work” and “7.…”
Section: Discussionmentioning
confidence: 99%
“…In this way, our concept with its underlying statements contributes to a new understanding of eHealth literacy. The concept also includes subjects previously identified to be essential to ensure usage of health technology [ 35 , 36 ], that is, trust that is embedded in the domains “4. Access to technologies that work” and “7.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, one of the reasons for high ratings might be that an overarching trust in a physician might be associated with patients’ trust and satisfaction in the physician's EHR use regardless of interaction style. A previous study also indicated that patient trust in physicians influences patients’ perceptions of physicians’ technology use (Montague & Asan, 2012). Another reason might be that patients mostly see only their physicians and assume their physicians’ interaction with the EHR is the ideal one, since they do not have a chance to compare with other physicians’ interaction styles.…”
Section: Discussionmentioning
confidence: 94%
“…ease of use and interaction style). These cues influence the patient’s perceptions of the work system as a whole and of individual system elements (Montague & Asan, 2012). The provider’s use of technology can also affect communicative behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…A study by Montague et al (2012) classified HCP behavior while using the EHR as technology-centered vs. human-centered and found that those who demonstrated human-centered behaviors had more positive verbal and non-verbal communication with patients compared with those who were focused more on typing and gazing at the computer. Poor communication between HCP and patients can also affect rapport, patient satisfaction, adherence to treatment, clinical outcomes, and patient trust (Shachak, Hadas-Dayagi, Ziv, & Reis, 2009;Tabler et al, 2014), highlighting the importance and need for solutions to preserve the connection that patients need with their providers.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…A strength from the analysis showed despite patients' concerns with security and privacy, patient's perceived quality of care fosters trust and builds the patientprovider relationship. The population may be willing to accept greater privacy risks as a trade-off for greater quality of care (Walker et al, 2017).Another study byMontague and Asan (2012) also investigated patient trust in health technology and the relationship with care providers. Data was collected from a Trust in Medical Technology instrument.…”
mentioning
confidence: 99%